2016
DOI: 10.1111/ijcs.12310
|View full text |Cite
|
Sign up to set email alerts
|

What are student preschool teachers learning about diet in their education in Norway?

Abstract: This article is based on a qualitative study on diet education among student preschool teachers. The problem under discussion is: What does a student preschool teacher learn in his education about food, meals, and nutrition? The material used in the article comprises interviews with student preschool teachers at one university and one college in Norway. Preschool teacher education is a three years university college study with bachelor degree. The survey results show that student preschool teachers do not rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…A research carried out in Greece also showed that the teachers had deficient knowledge of nutrients due to the structure of teachers training program [28]. Even in Norway, a survey of student preschool teachers highlighted the deficiency of curriculum in preparing these future teachers in dealing with their important task [29]. Identifying the gaps in care givers' education can turn stones and make a great difference in years ahead by addressing them [30].…”
Section: Resultsmentioning
confidence: 99%
“…A research carried out in Greece also showed that the teachers had deficient knowledge of nutrients due to the structure of teachers training program [28]. Even in Norway, a survey of student preschool teachers highlighted the deficiency of curriculum in preparing these future teachers in dealing with their important task [29]. Identifying the gaps in care givers' education can turn stones and make a great difference in years ahead by addressing them [30].…”
Section: Resultsmentioning
confidence: 99%
“…Defining the role of the teacher from a holistic, cyclical perspective views the teacher as an actor who takes a spiral approach to thinking and teaching. Both in terms of the interactions between teachers, children, and parents and in terms of the occurrence of time, the actions taken by the teacher are consistently repeated, re-examined, and reevaluated [1][2][3]. This non-linear spiral of ideas and proceeding steps is a trait of the early childhood teacher and is related to his/her view of children's learning, i.e., the idea that children construct knowledge in a spiral manner rather than in a linear or staged manner [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nini Wang. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] …”
unclassified